Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1007/s11284-018-1638-5
|View full text |Cite
|
Sign up to set email alerts
|

Different trends in phylogenetic and functional structure of plant communities along an elevation gradient

Abstract: The study of diversity gradients due to elevation dates back to the foundation of biogeography and ecology. Although elevation‐driven patterns of plant diversity have been reported for centuries, uncertainty still exists about the assembly rules that drive these patterns. In this study, we revealed the causal factor of community assemblies for the diversity of tree and herb species along an elevation. To this end, we applied an integrated method using both functional traits and phylogeny, called the mean pairw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 51 publications
0
3
1
Order By: Relevance
“…In our study, the NRI and NTI of plant communities with different forest strata showed a decrease with increasing altitude (Figure 4), indicating that the phylogenetic structure of the plant community was aggregated at low altitudes but tended to diverge at middle and high altitudes. These results contradict most studies that show low‐temperature filtering at high altitudes (Kitagawa et al, 2018; Qian et al, 2014; Zhang et al, 2021). However, some studies in the Rocky Mountains (Bryant et al, 2008) and on Mt.…”
Section: Discussioncontrasting
confidence: 93%
“…In our study, the NRI and NTI of plant communities with different forest strata showed a decrease with increasing altitude (Figure 4), indicating that the phylogenetic structure of the plant community was aggregated at low altitudes but tended to diverge at middle and high altitudes. These results contradict most studies that show low‐temperature filtering at high altitudes (Kitagawa et al, 2018; Qian et al, 2014; Zhang et al, 2021). However, some studies in the Rocky Mountains (Bryant et al, 2008) and on Mt.…”
Section: Discussioncontrasting
confidence: 93%
“…Furthermore, the phylogenetic and functional structure patterns along the elevation gradient were incongruent, an observation frequently discussed in past studies [ 24 , 62 ]. This pattern suggests that trait and phylogenetic weights may not be fixedly associated [ 58 ], implying that relying solely on phylogenetic or functional dimensions to reveal community structure is inefficient.…”
Section: Discussionmentioning
confidence: 97%
“…To adapt to the complex hydrothermal conditions in mid-elevation regions, plants have also evolved diverse functional properties ( Dıíaz and Cabido, 2001 ). However, the abundant species at higher elevations belonged to specific clades, and traits related to harsh environmental filtering at higher elevation evolved independently of phylogeny ( Kitagawa et al., 2018 ). Species that are able to overcome harsh environments and are common/dominant at high elevations have closer evolutionary distances, thus resulting in the relatively low phylogenetic diversity levels of common and dominant species at high elevations ( Webb et al., 2002 ; Qian, 2014 ; Kitagawa et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%